2016
DOI: 10.1159/000444487
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Stroke in Rural Gadchiroli, India: A Community-Based Study

Abstract: Background: In the near future, a majority of strokes are projected to occur in developing countries. However, population-level information on the prevalence of stroke from rural areas of developing countries, including India, is rare. We estimated the prevalence of stroke in a rural area of one of the most underdeveloped districts of India. Methods: Trained surveyors conducted a house-to-house survey using a validated screening questionnaire in a well-defined population of 45,053 living in 39 villages in a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 11 publications
(15 reference statements)
2
58
1
1
Order By: Relevance
“…However, an increase was observed in Sweden, Lund-Orup, between 1983–1985 and 2001–2002 [31]. Recently published data from the rural district of Gadchiroli, India, showed very high age-standardized prevalence of stroke (536 per 100,000 population) that doubled during the last 20 years [32]. Conclusively, report from the Global Burden of Disease 2010 showed that the age-standardized incidence of stroke significantly decreased by 12% (95% CI 6–17) in high-income countries from 1990–2010, along with non-significant increase by 12% (–3 to 22) in low-income and middle-income countries [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, an increase was observed in Sweden, Lund-Orup, between 1983–1985 and 2001–2002 [31]. Recently published data from the rural district of Gadchiroli, India, showed very high age-standardized prevalence of stroke (536 per 100,000 population) that doubled during the last 20 years [32]. Conclusively, report from the Global Burden of Disease 2010 showed that the age-standardized incidence of stroke significantly decreased by 12% (95% CI 6–17) in high-income countries from 1990–2010, along with non-significant increase by 12% (–3 to 22) in low-income and middle-income countries [33].…”
Section: Discussionmentioning
confidence: 99%
“…Close to two third of India's population lives in rural areas [4]. Studies conducted by us and others have shown that stroke has emerged as a major public health problem in rural areas of India [1,5,6]. In rural areas of Gadchiroli district in India, stroke was the leading cause of death and accounted for 14% of all deaths [5].…”
Section: Introductionmentioning
confidence: 99%
“…In rural areas of Gadchiroli district in India, stroke was the leading cause of death and accounted for 14% of all deaths [5]. Prevalence of stroke was also high (535/100,000 population) (6).…”
Section: Introductionmentioning
confidence: 99%
“…Роз-рив АА реєструється з частотою приблизно 9 ви-падків на 100 000 населення на рік, коливаючись від 2 на 100 000 у Китаї до 22,5 на 100 000 у Фін-ляндії, у США від САК щорічно страждають понад 30 тис. осіб [5][6][7][8][9][10]. Показники, що забезпечують ефективність хірургічного лікування АА ГМ -рання діагностика, глибинне обстеження стану хворого, вивчення топографоанатомічних особливостей будови судин ГМ, диференційний підхід до вибору методу хірургічного лікування, визначення його етапності та послідовності.…”
unclassified